A Pb isotope investigation of the Guli massif, Maymecha-Kotuy alkaline-ultramafic complex, Siberian flood basalt province, Polar Siberia - Kogarko, L. N.; Zartman, R. E. (Mineralogy and petrology, 2007)
Covering a vast area of the northern Siberian platform are the Siberian flood basalts (SFB), which make up one of the world's largest magmatic provinces. Along the northeastern margin of the SFB province lies the Maymecha-Kotuy alkaline-ultramafic complex, consisting of a large volume of alkaline lavas, numerous dykes, and the Guli massif together with numerous other, smaller alkaline plutons. The genetic link between the SFB and the Maymecha-Kotuy complex continues to be a subject of active debate. Although the rocks in both units have essentially the same age close to the Permian-Triassic boundary, questions remain as to the relative order of emplacement and the contributing source materials of each lithology. This study builds upon earlier petrologic, geochemical, and isotopic work to further an understanding of the relationship between SFB and alkaline rocks. A whole-rock U-Pb age of 250 +- 9Ma was determined for the Guli massif, which lies within the range of ages previously reported for the SFB. The Pb isotopic composition of the Guli rocks plot mainly in the lower portion of the OIB field, and dunite and carbonatite extend downward into the MORB field suggesting for them a more depleted source than the one that produced the SFB. The combined Pb, Sr, and Nd isotopic systematics of the SFB and the Guli alkaline rocks enable the identification of several discrete source components. The first component dominates many of the Guli rocks and is characterized by low 87Sr/86Sr (0.7031 to 0.7038), high [element of]Nd (+5.35 to +3.97), and relatively unradiogenic Pb (206Pb/204Pb = 17.88-18.31; 207Pb/204Pb = 15.38-15.46; 208Pb/204Pb = 37.33-37.70), which we associate with the depleted (MORB source) mantle. The second component representing most of the SFB demonstrates a notable chemical and isotopic uniformity with 87Sr/86Sr values of 0.7046 to 0.7052, [element of]Nd values of 0 to +2.5, and an average Pb isotopic composition of 206Pb/204Pb = 18.3, 207Pb/204Pb = 15.5, and 208Pb/204Pb = 38.0. This component, making up the majority of SFB, is speculated to be a relatively primitive lower mantle plume with a near-chondritic signature. Contamination by upper and lower continental crustal material, designated as components 3 and 4, is postulated to explain the isotopic characteristics of some of the higher SiO2 Guli rocks and SFB. Finally, metasomatic processes associated with the invasion of the Siberian super-plume add a fifth component responsible for the extreme enrichment in rare-earth and related elements found in some Guli rocks and SFB. [PUBLICATION ABSTRACT]